Evolution of Men's Image in Fashion Advertising: Breaking Stereotypes and Embracing Diversity. - Carrasco-Santos, María Jesús; Cristófol-Rodríguez, María del Carmen; Begdouri- Rodríguez, Ismael (MDPI, 2024)
Abstract: Investigates whether societal and fashion evolution has contributed to a departure from traditional stereotypes. The research methodology comprised three phases: content analysis, surveys, and in-depth interviews with an expert panel, examining how men’s clothing has been communicated in fashion over a span of 50 years, with a focus on three renowned brands: Lacoste, Burberry, and Hugo Boss. The findings reveal a notable shift in fashion advertising targeting men, characterized by increased racial diversity among models and a more diverse depiction of attitudes and poses. However, homosexual or bisexual couples remain largely unrepresented. The study highlights the influence of advertising on shaping the image of the “new man”, evident through the diminishing gender boundaries in clothing and accessories and the persistent struggle to break free from stereo- types. The study underscores the significance of ongoing efforts to promote diversity and inclusivity in fashion advertising
Keywords: Moda - Aspectos sociales; Men’s representation; Fashion evolution; Stereotype; Clothing communication; Diversity and inclusion; Societal impact